Impact of the 2019/2020 Australian Megafires on Air Quality and Health. (22nd October 2021) - Graham, Ailish M.; Pringle, Kirsty J.; Pope, Richard J.; Arnold, Stephen R.; Conibear, Luke A.; Burns, Helen; Rigby, Richard; Borchers‐Arriagada, Nicolás; Butt, Edward W.; Kiely, Laura; Reddington, Carly; Spracklen, Dominick V.; et al.
Abstract: The Australian 2019/2020 bushfires were unprecedented in their extent and intensity, causing a catastrophic loss of habitat, human and animal life across eastern‐Australia. We use a regional air quality model to assess the impact of the bushfires on particulate matter with a diameter less than 2.5 μm (PM2.5 ) concentrations and the associated health impact from short‐term population exposure to bushfire PM2.5 . The mean population Air Quality Index (AQI) exposure between September and February in the fires and no fires simulations indicates an additional ∼437, 000 people were exposed to "Poor" or worse AQI levels due to the fires. The AQ impact was concentrated in the cities of Sydney, Newcastle‐Maitland, Canberra‐Queanbeyan and Melbourne. Between October and February 171 (95% CI: 66–291) deaths were brought forward due to short‐term exposure to bushfire PM2.5 . The health burden was largest in New South Wales (NSW) (109 (95% CI: 41–176) deaths brought forward), Queensland (15 (95% CI: 5–24)), and Victoria (35 (95% CI: 13–56)). This represents 38%, 13% and 30% of the total deaths brought forward by short‐term exposure to all PM2.5 . At a city‐level 65 (95% CI: 24–105), 23 (95% CI: 9–38) and 9 (95% CI: 4–14) deaths were brought forward from short‐term exposure to bushfire PM2.5, accounting for 36%, 20%, and 64% of the total deaths brought forward from all PM2.5. Thus, the bushfires caused substantial AQ and health impacts across eastern‐Australia. Climate change is projected to increase bushfire risk, therefore future fire management policies should consider this. Plain Language Summary: The Australian 2019/2020 bushfires were unprecedented in their size and intensity, resulting in a catastrophic loss of habitat and human and animal life across eastern‐Australia. We use an air pollution model (WRF‐Chem) to quantify the impact of the bushfires on particulate matter with a diameter less than 2.5 μm (PM2.5 ) concentrations. We run the model with and without emissions from the fires so their impact on PM2.5 can be isolated. We find that between September and February an additional ∼437, 000 people were exposed to "Poor" or worse air quality index levels due to the fires across eastern‐Australia. Short‐term exposure to high PM2.5 concentrations has been linked to negative health impacts. Therefore, we estimate the health impact of population exposure to bushfire PM2.5 across eastern‐Australia, regionally and at city level. Our estimate indicates that between October and February 171 deaths were brought forward due to exposure to PM2.5 from the fires. Regionally, most deaths were brought forward in New South Wales (109 deaths brought forward), Queensland (15), and Victoria (35). Within these regions, the most deaths were brought forward in Sydney (65), Melbourne (23), and Canberra‐Queanbeyan (9) as large populations were exposed to high PM2.5 concentrations due to the bushfires. Key Points: The fires led to widespread exposure to "Poor" or worse Air Quality Index levels across eastern‐Australia The highest all‐cause, all‐age mortality from short‐term exposure to bushfire particulate matter with a diameter less than 2.5 μm (PM2.5 ) was seen in the states of New South Wales, Queensland, and Victoria All‐cause, all‐age mortality from short‐term exposure to bushfire PM2.5 was highest in the cities of Sydney, Melbourne, and Canberra